Gambling and State intervention: individual choice from the perspective of freedom in John Stuart Mill - Bezerra de Lima, Alícia Regianne; Azevedo Rodrigues, Fillipe (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
This article discusses the criminal intervention of the state in the economic order based on a philosophical, constitutional and financial analysis of the exploitation and non-regulation of games of chance in Brazil. It also considers the impact of modern technologies on online gambling and the additional challenges to state regulation. Initially, it addresses freedom, its limits and the figure of the state, in the light of John Stuart Mill’s ideas, relating individual choices and state interference in the face of economic activity that the state intervenes in, criminalizes and, at the same time creates its monopoly. Through a legislative evaluation, it relates articles 170 and 173 of the Constitution and the exceptional hypotheses of state intervention, addresses the Law on Criminal Contraventions, the Money Laundering Law, and points out the unconstitutionality of interventions that reach and interrupt individual freedoms.